Integrating a complex late prehistoric settlement system: Neutron activation analysis of pottery use and exchange at Saruq al-Hadid, United Arab Emirates. (December 2018) - Karacic, Steven; Weeks, Lloyd; Cable, Charlotte; Méry, Sophie; al-Ali, Yaaqoub; Boraik, Mansour; Zein, Hassan; Glascock, Michael D.; MacDonald, Brandi L.
Abstract: Temporary sites were a critical component of the prehistoric Near Eastern economy but, because of their ephemeral nature, are less frequently the focus of research than sedentary settlements. The present article presents the results of neutron activation analysis conducted on pottery from the temporary site of Saruq al-Hadid, United Arab Emirates. The results identified both continuity and change in the pottery consumed at the site in the Bronze and Iron Ages, which suggests that the peoples gathering here were integrated into economic practices observed at sedentary sites throughout southeastern Arabia. Highlights: Compositional analysis of ceramics has prioritized sedentary sites Temporary sites were integrated into social and economic systems Ceramics from a temporary site provide evidence for the integration of the settlement system Evidence from sedentary sites alone overlooks the continuity evident at this temporary site